Policy evaluation of movement to build prosperous, independent and dignified villages program in Pasangkayu District - Hartawan, Hartawan; Hasanuddin, Hasanuddin; Samsu, M. Kafrawi Al- Kafiah (Technium Social Sciences Journal, 2021)
This study aims to examine and analyze the extent of achievements resulting from the Policy Evaluation of the Prosperous, Independent, and Dignified Village Development Movement (GEMA D’SMART) program in Pasangkayu District, Pasangkayu Regency. This research is designed qualitatively with descriptive type of research. The number of informants in this study was 5 people assigned with purposive techniques. The data needed in this study are secondary data and primary data. Secondary data is obtained from documentation studies in the field while primary data is obtained through observations and interviews. Because this research uses descriptive research type, the analysis technique is qualitative. The results showed that the Policy of The Movement to Build Prosperous, Independent and Dignified Villages (GEMA D'SMART) in Pasangkayu Sub-district has not been effective (optimal) in the implementation process, especially judging by the criteria or indicators of effectiveness where the implementation time of GEMA D'SMART program often occurs delays and diversion / transfer of programs to other places due to natural conditions (flooding or overflow of Pasangkayu river). In addition, the alignment criteria of this program have not been carried out evenly where there are two villages in Pasangkayu District have not been touched by this program. While from the indicators/criteria of responsiveness and accuracy, GEMA D'SMART program provides positive impacts and benefits in accelerating the equalization of development implementation and improvement of rural community welfare, moreover, this program is prepared by the community itself with SKPD, especially the Agriculture Office.